النحو ونشأته عند البصريين والكوفيين - Ahmad Bachmid (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2000)
Al Nahwu wa Nasy-atihi 'Inda Al Basriyyin wa Al Kuffiyyin